REVITALISASI OBJEK WISATA DALAM MENINGKATKAN PARIWISATA DI DESA SIGAPITON KEC, AJIBATA KAB, TOBA PROV, SUMATERA UTARA - Rahul Depri Simanjuntak; Jan Hary Siburian; Win Fronstein Naibaho; Tambos August Sianturi (Abdi Jurnal Publikasi, 2025)
Sigapiton is one of the villages in Ajibata District, Toba Regency, with an area of ​​70.80 km² (BPS, 2018). Sigapiton Village consists of Hamlet I (Lumban Butar-butar 1 and Lumban Butar-butar 2), Hamlet II (Sosor Dolok, Sosor Baringin, Lumban Nauli, Lumban Hasatan). Sigapiton Village has a total of 175 heads of families, assuming that each family has 4-7 people. Community Service Lectures (KPPM) are a form of practical learning activities in the context of applying interdisciplinary knowledge which students carry out directly in the community. This tourist attraction revitalization activity begins by explaining the purpose of the service, namely so that the community can take advantage of the tourist attraction in order to increase the number of tourists visiting the village. By carrying out the revitalization of this tourist attraction in Sigapiton Village, it is hoped that it will be able to encourage local residents, especially Sigapiton residents, to maintain and develop this tourist attraction.